2017
DOI: 10.1002/chem.201704337
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of P2BCh Ring Systems (Ch=S, Se) and Their Reactivity with N‐Heterocyclic Carbenes

Abstract: Four-membered rings with a P BCh core (Ch=S, Se) have been synthesized by the reaction of phosphinidene chalcogenide (Ar*P=Ch) and phosphaborene (Mes*P=BNR ). The mechanistic pathways towards these rings are explained by detailed computational work that confirmed the preference for the formation of P-P, not P-B, bonded systems, which seems counterintuitive given that both phosphorus atoms contain bulky ligands. The reactivity of the newly synthesized heterocycles, as well as that of the known (RPCh) rings (n=2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 78 publications
1
28
1
2
Order By: Relevance
“…Ragogna and co‐workers discovered that the related phosphinidene selenides (RP=Se) n can be used as phosphorus source and treated the phosphinidene selenide dimer (DmpP=Se) 2 (Dmp = 2,6‐dimesitylphenyl) with 4 equivalents of 1,3,4,5‐tetramethylimidazol‐2‐ylidene ( 2 ) or 1,3‐diisopropyl‐4,5‐dimethylimidazol‐2‐ylidene ( 4 ) to afford the NHC=PR adducts 2· P(Dmp) ( δ 31 P = –76.7) and 4· P(Dmp) ( δ 31 P = –75.0) in 44 and 66 % yield, respectively, together with the corresponding selenoureas (Scheme ) . The phosphinidene selenide trimer (DmpP=Se) 3 works equally well as phosphinidene synthon and yields 2· P(Dmp).…”
Section: Synthesis Of N‐heterocyclic Carbene–phosphinidene Adductsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ragogna and co‐workers discovered that the related phosphinidene selenides (RP=Se) n can be used as phosphorus source and treated the phosphinidene selenide dimer (DmpP=Se) 2 (Dmp = 2,6‐dimesitylphenyl) with 4 equivalents of 1,3,4,5‐tetramethylimidazol‐2‐ylidene ( 2 ) or 1,3‐diisopropyl‐4,5‐dimethylimidazol‐2‐ylidene ( 4 ) to afford the NHC=PR adducts 2· P(Dmp) ( δ 31 P = –76.7) and 4· P(Dmp) ( δ 31 P = –75.0) in 44 and 66 % yield, respectively, together with the corresponding selenoureas (Scheme ) . The phosphinidene selenide trimer (DmpP=Se) 3 works equally well as phosphinidene synthon and yields 2· P(Dmp).…”
Section: Synthesis Of N‐heterocyclic Carbene–phosphinidene Adductsmentioning
confidence: 99%
“…Ragogna and co‐workers reacted 4· P(Dmp) ( δ 31 P = –75.0) with the strongly Lewis acidic B(C 6 F 5 ) 3 in THF, which results in controlled ring‐opening of THF affording product 27 ( δ 31 P = –24.7; Scheme ) …”
Section: Reactivity Of N‐heterocyclic Carbene–phosphinidene Adductsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further reactivity of 38 showed that it could be used to access mixed main group element rings (Compounds 42 and 43 , Scheme 9). [73] …”
Section: Group 13 Multiple Bondsmentioning
confidence: 99%
“…N‐heterocyclic carbene‐phosphinidene adducts have found numerous applications in diverse fields such as the frustrated Lewis acid‐base pair chemistry, for example in the activation and ring‐opening of THF, and as new ligands in coordination chemistry . Furthermore, Grützmacher et al reported that treatment of the Lewis adduct of a zinc(II) complex such as [{(IMe)PPh}(ZnCl 2 (thf)]] 2 with a series of organic acceptors phenanthrene‐9,10‐quinone, diphenylketene, and trans ‐chalocone yielded the corresponding organophosphorus compounds by transfer and insertion of the PPh moiety .…”
Section: Introductionmentioning
confidence: 99%